Решить уравнение методом введения новой переменной
x/(x²-2)+6*(x²-2)/x = 7
ответ: { - 4/3 , - 1 , 3/2 , 2 } * * * { -1 1/3 ; - 1 ; 1,5 ; 2 } * * *
Объяснение: x/(x²-2)+6*(x²-2)/x =7
ОДЗ: { x≠0 ; x²-2≠ 0 . ⇔ x≠ { -√2 ; 0; √2 }
замена: t =x/(x²-2)
t + 6 /t =7 || t≠0 || ⇔t² -7t + 6=0 ⇒ t₁ =1 ,t₂= 6 ( По теореме Виета )
Обратная замена
а) x/(x²-2) =1 ⇔ x= x²-2 ⇔x²-x-2 =0 ⇒ x₁ = - 1 , x₂= 2 ;
б) x/(x²-2) =6 ⇔ 6x² - x - 12 =0 D = 1² -4*6*(-12)=289 =17²
x₃,₄ =(1 ±17) /( 2*6) x₃ =(1-17)/12 = - 4/3 , x₄ = 3/2.
2х^2+14х-3х-21=2х^2-3х+8х-12+3
14х-21=8х-12+3
14х-21=8х-9
14х-8х=-9+21
6х=12
х=2
2х+9/4-х-2/6=3
х+23/12=3
х=3-23/12
х=13/12